A novel substitution in NS5A enhances the resistance of hepatitis C virus genotype 3 to daclatasvir. (3rd January 2021) - Fernandes Campos, Guilherme Rodrigues; Ward, Joseph; Chen, Shucheng; Bittar, Cintia; Vilela Rodrigues, João Paulo; Martinelli, Ana de Lourdes Candolo; Souza, Fernanda Fernandes; Pereira, Leonardo Régis Leira; Rahal, Paula; Harris, Mark
Abstract : Hepatitis C virus (HCV) genotype 3 presents a high level of both baseline and acquired resistance to direct-acting antivirals (DAAs), particularly those targeting the NS5A protein. To understand this resistance we studied a cohort of Brazilian patients treated with the NS5A DAA, daclatasvir and the nucleoside analogue, sofosbuvir. We observed a novel substitution at NS5A amino acid residue 98 [serine to glycine (S98G)] in patients who relapsed post-treatment. The effect of this substitution on both replication fitness and resistance to DAAs was evaluated using two genotype 3 subgenomic replicons. S98G had a modest effect on replication, but in combination with the previously characterized resistance-associated substitution (RAS), Y93H, resulted in a significant increase in daclatasvir resistance. This result suggests that combinations of substitutions may drive a high level of DAA resistance and provide some clues to the mechanism of action of the NS5A-targeting DAAs.